Praying with the Songs of Taize - Émile, Frère (Edinost in dialog, 2024)
The article retraces the origin and the development of prayer with Taizé songs that has spread throughout the world. The various components of this style of prayer and why it speaks to contemporary mentalities are examined along with the insights of liturgists, theologians and the philosopher Paul Ricoeur who was a frequent visitor to Taizé.